2013
DOI: 10.1016/j.jceh.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence and More Severe Coronary Artery Disease in Hepatitis C Virus-infected Patients: A Case Control Study

Abstract: Background: An association of Coronary artery disease (CAD) with hepatitis C (HCV) has been suggested, but definitive data are still lacking. Aim: Our study sought to estimate the prevalence and severity of CAD in HCV patients compared to with age-, sex-, and race-matched controls without HCV infection. Subjects and methods: 63 HCV-infected patients were compared with 63 age, race, and sex-matched controls without HCV infection undergoing coronary angiography for evaluation of CAD. CAD was defined as more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
(21 reference statements)
3
10
0
Order By: Relevance
“…(39,40) The association between HCV infection and cardiovascular events is a contentious issue. Several observational studies have found that in the general population, HCV is an independent factor associated with coronary artery disease, (41)(42)(43)(44)(45) stroke, (39,46,47) and peripheral artery disease. (48) HCV infection has also been found to increase the likelihood of cardiovascular disease among HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…(39,40) The association between HCV infection and cardiovascular events is a contentious issue. Several observational studies have found that in the general population, HCV is an independent factor associated with coronary artery disease, (41)(42)(43)(44)(45) stroke, (39,46,47) and peripheral artery disease. (48) HCV infection has also been found to increase the likelihood of cardiovascular disease among HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In another study carried out among patients included in the Veterans Aging Cohort Study-Virtual Cohort (VACS-VC), HIV-infected women had increased rates and risk of incident cardiovascular disease events, as compared to uninfected women, after adjustment for demographics, Framingham risk factors, other comorbidities, and substance use and abuse [39 && ]. Several observational studies in the last 2 years have found that HCV infection is an independent factor associated with coronary artery disease events including a study from the VACS-VC [40], HCV infection was also found to be independently associated with an increased hazard of acute myocardial infarction in a case-control study from a clinical center in New York [41], a retrospective cohort from the University of Arkansas [42], and two cross-sectional studies performed in Taiwan [43] and Denmark [44]. However, in a systematic review of casecontrol and cohort studies published from 1995 to 2013, the association between chronic HCV infection and coronary artery disease was concluded to remain unclear [45].…”
Section: Atherosclerosis and Cardiovascular Diseasementioning
confidence: 95%
“…Alyan et al 11 used a modified Reardon severity scoring system and demonstrated that CAD severity scores were significantly higher in the HCV seropositive group than in the control group ( p < 0.001), and HCV seropositivity was an independent predictor for the severity of coronary atherosclerosis (OR: 2.018, 95% CI: 1.575–2.579; p < 0.001) after adjustment for age, sex, smoking, hypertension, DM, body mass index (BMI), CRP and fibrinogen. 11 In patients undergoing coronary angiography for evaluation of CAD, Satapathy et al 63 observed a significantly higher prevalence of CAD (69.8% vs. 47.6%, p = 0.01), significantly higher modified Reardon’s severity scores (6.26 ± 5.39 vs. 2.6 ± 3.03, p < 0.0005), and significant multivessel CAD (defined as >50% stenosis in ≥2 vessels involved; 57.1% vs. 15.9%, p < 0.0005) among the HCV-infected patients compared to controls. Salam et al 64 reported that HCV antibody-positive patients had more severe coronary lesions than seronegative patients among those referred for angiography.…”
Section: Hcv and Angiographic Cadmentioning
confidence: 99%